2018
DOI: 10.1177/2397791418768576
|View full text |Cite
|
Sign up to set email alerts
|

Modeling creep behavior of carbon nanotube/fiber/polymer composite cylinders

Abstract: In this research, the effects of multi-walled carbon nanotubes on the distribution of long-term creep strains in thickwalled multi-walled carbon nanotube/fiber/polymer three-phase laminated composites are studied. In the first step, micromechanical models are developed to calculate the elastic properties of multi-walled carbon nanotube/vinylester and multi-walled carbon nanotube/E-glass fiber/vinylester composites. Using classical lamination plate theory, equilibrium and compatibility equations and strain-disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In this comparison, fiber orientation is α=45° and weight fractions is 4.5%, and results after 10 years are investigated. Figure 3 demonstrated the comparison distribution of the radial and circumferential creep strain in the wall of cylinder in present study and other results [23]. It is clear that there is good agreement between these results.…”
Section: Numerical Results and Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In this comparison, fiber orientation is α=45° and weight fractions is 4.5%, and results after 10 years are investigated. Figure 3 demonstrated the comparison distribution of the radial and circumferential creep strain in the wall of cylinder in present study and other results [23]. It is clear that there is good agreement between these results.…”
Section: Numerical Results and Discussionsupporting
confidence: 78%
“…To demonstrate the accuracy of the present solution, a comparison has been made between the present study and the previous work studied by Ghasemi et al. [23], and the effects of MWCNTs on the distribution of long-term creep strains in thick-walled MWCNTs/glass fiber(GF)/polymer three-phase laminated composites are studied. The nano-composite assumed is made of MWCNTs/GF/vinylester with unidirectional material, and mechanical and thermal properties are shown in Table 2.…”
Section: Numerical Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…He reported that the creep profiles at 50°C show better stress transfer than 110°C, due to induced tensile stresses at high temperature. Ghasemi et al modeled the creep behavior of CNT in glass fiber vinyl ester composite and reported that the addition of CNT can reduce absolute values of the radial and circumferential creep strains and dimensionless effective stresses. In general creep in FRP composite is mostly driven by the matrix phase, and hence matrix modification may be thought of a potential way to improve the creep performance of FRP composite.…”
Section: Introductionmentioning
confidence: 99%